A comparison of the effects of different stretching methods on flexibility, muscle activity, and pain threshold in ballet dancers; a preliminary randomized controlled trial. Issue 4 (October 2020) - Ko, Min Gyun; Lee, Myung Mo; Song, Chang Ho
Abstract: Background: The purpose of this study is to compare the effects of stretching methods on flexibility, muscle activation, and pressure pain threshold in ballet dancers, and to suggest an effective stretching method. Methods: Thirty-three ballet dancers were randomized to the static stretching group ( n  = 11), muscle energy technique stretching group ( n  = 11), and vibration-assisted stretching group ( n  = 11). The angle of hip joint extension in arabesque, activation of the rectus femoris in devéloppé, and pressure pain threshold on the rectus femoris in the sitting position were measured to compare the effects of the different stretching methods. Paired t -test was used to compare the pre and post-intervention findings within each group and one-way analysis of variance to compare the difference in the amount of changes among the groups. Results: The hip joint extension angles increased in all stretching methods ( p  < 0.05); however, vibration-assisted stretching and muscle energy technique stretching were more effective than static stretching ( p  < 0.05). The activation of the rectus femoris decreased in all groups ( p  < 0.05); however the muscle energy technique stretching group and vibration-assisted stretching group showed a significant decrease in muscle activation compared with the static stretching group ( p  < 0.05). The pressure pain threshold significantly improved only in the static stretching group (p  < 0.05); and vibration-assisted stretching group (p  < 0.05). Conclusions: Compared with static stretching and muscle energy technique stretching, vibration-assisted stretching is a beneficial method for improving flexibility, muscle activation, and pressure pain threshold in ballet dancers.